Islām wa fiqh Nusantara: al-Tanāfus ‘alá al-huwīyah wa ‘alāqat al-sulṭah wa al-ramz al-dīnī li jam‘īyah Nahdlatul Ulama - Muhammad Noor Harisudin (Studia Islamika, 2017)
This article tries to explain how the debate of Islam Nusantara and Fiqh Nusantara discourses among internal Nahdlatul Ulama (NU) happened. The debate, in fact, not only comes from the external of NU’s adherents, but also from the inner-circle of NU’s followers. In the 2015 NU Congress in Jombang, East Java, the debate was polarized into two main groups, namely the traditional ulama and the liberal ulama. The liberal group of NU as represented by Said Aqil Siradj, the General Chairman of PBNU for two periods (2010-2015 and 2015-2020) has been considered as a group of Islam Nusantara bearer, while Hasyim Muzadi, the former General Chairman of PBNU (1999-2004 and 2004-2010) has been considered as a representation of traditional group who reject the concept of Islam Nusantara. This study finds that the debate is not solely about the Islam Nusantara content, but it relates to the power relations among NU’s elite in identifying NU organization with the others to seize the symbols of “power” within NU organization.DOI: 10.15408/sdi.v24i3.4324